Optimalisasi Pemasaran Dan Penjualan Jamu Karya Jaya Melalui Pemanfaatan Website Di Kelurahan Karya Jaya Kota Tebing Tinggi: Indonesia - Muthia Ferliani Balqis; Citra Dewi Hasibuan; Yan Batara Putra Siringoringo; Enita Dewi Br Tarigan (Jurnal Mitra Prima, 2026)
Karya Jaya Village is a village located in Rambutan District, Tebing Tinggi City, North Sumatra Province, Indonesia, which is famous for its herbal medicine (jamu). The Jamu Karya Micro, Small, and Medium Enterprise (MSME) is processed from traditional ingredients, a cultural heritage of Indonesia that has been used for generations as a herbal drink to maintain health and treat various diseases. In recent years, it has experienced obstacles in marketing and selling its products. One of the main factors is the lack of quality human resources in the marketing and sales fields, resulting in a lack of effective marketing strategies. The solution to this problem is training to improve the quality of human resources and product marketing to consumers, as well as the use of technology in product marketing using a website.